The Authority of the Selection Working Group in the Implementation of the Direct Appointment Method in the Procurement of Consulting Services: A Legal Perspective at the Palembang Aviation Polytechnic - Abdul Latif Mahfuz; Dedy Aryanto; Romli SA; Saparyanto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Procurement of goods and services in the public sector requires special attention to compliance with applicable laws and regulations, especially in terms of implementing procurement methods. One method used is direct appointment, which allows the Selection Working Group to appoint service providers without going through an open auction, with certain conditions. This study aims to analyze the authority of the Selection Working Group in implementing direct appointment in the procurement of consulting services at the Palembang Aviation Polytechnic, as well as to examine its implementation from the perspective of applicable law. This study uses a normative legal method with a statutory approach and case studies, involving an analysis of related laws and regulations, procurement documents, and interviews with related parties. The results of the study indicate that although direct appointment can be applied under certain conditions, its implementation at the Palembang Aviation Polytechnic often experiences obstacles in terms of transparency and accountability. This study also found that the authority of the Selection Working Group needs to be strengthened with stricter supervision to ensure that legal principles are maintained. The recommendations put forward are the need to improve understanding and training for members of the Selection Working Group and improvements in internal oversight mechanisms to optimize the implementation of procurement in accordance with legal provisions.